A Doll's House - Ibsen, Henrik (Lahore New Kitab Mahal, 2007)
A Doll's House, the three-act play by Henrik Ibsen, which premiered at the Royal Theatre in Copenhagen, Denmark in 1879, is one of the most well-known and frequently performed of modern plays.
Keywords: Domestic drama, Norwegian